Marginal notes on Chadic lexical roots with *n- (Addenda et corrigenda to O.V. Stolbova’s Chadic Lexical Database, Issue I: L, N, NY, R) - Takács, Gábor (Acta Orientalia Vilnensia, 2008)
Hungarian Academy of ScienceEötvös Loránd UniversityThis paper examines the Afro-Asiatic etymologies of Chadic lexical roots discussed by Olga V. Stolbova in her Chadic Lexical Database, Issue I (2005). The analysis is arranged according to the following sections: (1) Common Chadic reconstructions, (2) Isolated Chadic roots that nevertheless have Afro-Asiatic cognates. The paper represents the third part of my longer series of papers on addenda et corrigenda to Chadic lexical roots.